Minos and the moderns : Cretan myth in twentieth-century literature and art - Ziolkowski, Theodore (Classical presences, 2008)
This work considers three mythological complexes that enjoyed a unique surge of interest in early 20th-century European art and literature: Europa and the bull, the minotaur and the labyrinth and Daedelus and Icarus.